Apertura ontológica y lucha anticolonial en la soberanía alimentaria: un diálogo con las perspectivas indígenas de Abya Yala - Giovanna Micarelli (e-cadernos ces)
Discussions around food sovereignty in indigenous contexts show some frictions in how food sovereignty is understood and practiced, beginning with the meaning of both “sovereignty” and “food”. These frictions invite us to scrutinize concepts we take for granted. Through a review of recent transformations of the concept of food sovereignty and a dialogue with the worldviews of several indigenous societies of the Americas, this article aims to respond to the challenges raised by alternatives ontologies to expand the possibilities of an anticolonial social transformation. In particular, it seeks to incorporate into the discussion on rights those forms of relating to the world that do not fit into the ontological separation between humans and nature and subject and object established by the dominant Western modernity. This separation has structured, on the one hand, the understanding of “natural resources” as objects, and on the other, the notion of rights as something inherent to the person.